Crowded developmental environment promotes adult sex-specific nutrient consumption in a polyphagous fly - Juliano Morimoto; Binh Nguyen; Hue Dinh; Anh The Than; Phillip W. Taylor; Fleur Ponton (Frontiers in Zoology, 2019)
Abstract Background The fitness of holometabolous insects depends largely on resources acquired at the larval stage. Larval density is an important factor modulating larval resource-acquisition, influencing adult survival, reproduction, and population maintenance. To date, however, our understanding of how larval crowding affects adult physiology and behaviour is limited, and little is known about how larval crowding affects adult non-reproductive ecological traits. Here, larval density in the rearing environment of the polyphagous fruit fly Bactrocera tryoni (‘Queensland fruit-fly’) was manipulated to generate crowded and uncrowded larval treatments. The effects of larval crowding on pupal weight, adult emergence, adult body weight, energetic reserves, fecundity, feeding patterns, flight ability, as well as adult predation risk were investigated. Results Adults from the crowded larval treatment had lower adult emergence, body weight, energetic reserves, flight ability and fecundity compared to adults from the uncrowded larval treatment. Adults from the crowded larval treatment had greater total food consumption (i.e., consumption of yeast plus sucrose) relative to body weight for both sexes compared to adults from the uncrowded treatment. Furthermore, males from the crowded treatment consumed more yeast relative to their body weight than males from the uncrowded treatment, while females from the crowded treatment consumed more sucrose relative to their body weight than females from the uncrowded treatment. Importantly, an interaction between the relative consumptions of sucrose and yeast and sex revealed that the density of conspecifics in the developmental environment differentially affects feeding of adult males and females. We found no effect of larval treatment on adult predation probability. However, males were significantly more likely to be captured by ants than females. Conclusion We show that larvae crowding can have important implications to ecological traits in a polyphagous fly, including traits such as adult energetic reserve, flight ability, and adult sex-specific nutrient intake. Our findings contextualise the effects of larval developmental conditions into a broad ecological framework, hence providing a better understanding of their significance to adult behaviour and fitness. Furthermore, the knowledge presented here can help us better understanding downstream density-dependent effects of mass rearing conditions of this species, with potential relevance to Sterile Insect Technique.